Pengembangan Media Pembelajaran Multimedia Interaktif Pilar Baru (Pintar Belajar Bangun Ruang) pada Siswa Kelas VIII - Ismail T; Usman Mulbar; Asdar (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
The purposes of this development research to develop interactive multimedia-based learning media Pilar Baru (Pintar Belajar Bangun Ruang) and describe the quality of media based on aspects of validity, practicality, and effectiveness. The design of this study refers to the ADDIE development model which includes 5 stages, namely analysis, design, development, implementation, and evaluation. The research instruments were in the form of media assessment sheets by material experts, media experts, and teachers to measure practicality. and learning outcomes test questions to measure media effectiveness. Product testing was conducted on 36 students of class VIII. The results showed that the assessment by the material and media experts was obtained an average score 4.29 then the teacher obtained an average score of 4.4 with very good criteria so that the developed media was declared valid. The results of the questionnaire response analysis of students obtained an average score of 4.57 and the teacher's response obtained an average score of 4.62 with very good criteria. The results of observations of the implementation of learning showed a very good classification with a percentage reaching 96.87%. The percentage of classical completeness from student learning outcomes tests reached 80.6% so the media was declared effective.